Overexpression of SLIM1 transcription factor accelerates vegetative development in Arabidopsis thaliana - Apodiakou, Anastasia; Alseekh, Saleh; Hoefgen, Rainer; Whitcomb, Sarah J. (Frontiers in Plant Science, 2024)
The transcription factor Sulfur Limitation 1 (SLIM1) belongs to the plant-specific Ethylene Insenstive3-Like transcription factor family and is known to coordinate gene expression in response to sulfur deficiency. However, the roles of SLIM1 in nutrient-sufficient conditions have not been characterized. Employing constitutive SLIM1 overexpression (35S::SLIM1) and CRISPR/Cas9 mutant plants (slim1-cr), we identified several distinct phenotypes in nutrient-sufficient conditions in Arabidopsis thaliana. Overexpression of SLIM1 results in plants with approximately 2-fold greater rosette area throughout vegetative development. 35S::SLIM1 plants also bolt earlier, and exhibit earlier downregulation of photosynthesis-associated genes and earlier upregulation of senescenceassociated genes than Col-0 and slim1-cr plants. This suggests that overexpression of SLIM1 accelerates development in Arabidopsis thaliana. Genome wide differential gene expression analysis relative to Col-0 at three timepoints with slim1-cr and two 35S::SLIM1 lines allowed us to identify 1731 genes regulated directly or indirectly by SLIM1 in vivo.